Role of social relations of outside directors with CEO in earnings management - Muhammad Shaique; Fei Guo; Ruqia Shaikh; Shahbaz Khan; Muhammad Usman (International Journal of Financial Studies, 2017)
The purpose of this study is to examine the impact of social relations among the board members on earnings management in Pakistani listed companies. Specifically, we have analyzed the social networks between CEO and outside board members. The modified Jones model has been used in this study to measure earnings management and we have captured social relations through SOCIAL (Social networking index). Our results suggest that firms with more connected boards show a positive relationship between board independence and earnings management. Further, we have shown that firms with CEO duality exhibit a higher association between social connections of the board and earnings management than firms with non-duality. Social relations among the board members undermine monitoring ability of outside directors and the impact becomes more severe in the presence of CEO duality.
Keywords: M41; M48; 330; social relations; earnings management; CEO duality; outside directors